A proteomic study of resistance to Brown Ring disease in the Manila clam, Ruditapes philippinarum. Issue 99 (April 2020) - Smits, M.; Artigaud, S.; Bernay, B.; Pichereau, V.; Bargelloni, L.; Paillard, C.
Abstract: Marine mollusk aquaculture has more than doubled over the past twenty years, accounting for over 15% of total aquaculture production in 2016. Infectious disease is one of the main limiting factors to the development of mollusk aquaculture, and the difficulties inherent to combating pathogens through antibiotic therapies or disinfection have led to extensive research on host defense mechanisms and host-pathogen relationships. It has become increasingly clear that characterizing the functional profiles of response to a disease is an essential step in understanding resistance mechanisms and moving towards more effective disease control. The Manila clam, Ruditapes philippinarum, is a main cultured bivalve species of economic importance which is affected by Brown Ring disease (BRD), an infection induced by the bacterium Vibrio tapetis . In this study, juvenile Manila clams were subjected to a 28-day controlled challenge with Vibrio tapetis, and visual and molecular diagnoses were carried out to distinguish two extreme phenotypes within the experimental clams: uninfected ("RES", resistant) and infected ("DIS", diseased) post-challenge. Total protein extractions were carried out for resistant and diseased clams, and proteins were identified using LC-MS/MS. Protein sequences were matched against a reference transcriptome of the Manila clam, and protein intensities based on label-free quantification were compared to reveal 49 significantly accumulated proteins in resistant and diseased clams. Proteins with known roles in pathogen recognition, lysosome trafficking, and various aspects of the energy metabolism were more abundant in diseased clams, whereas those with roles in redox homeostasis and protein recycling were more abundant in resistant clams. Overall, the comparison of the proteomic profiles of resistant and diseased clams after a month-long controlled challenge to induce the onset of Brown Ring disease suggests that redox homeostasis and maintenance of protein structure by chaperone proteins may play important and interrelated roles in resistance to infection by Vibrio tapetis in the Manila clam. Highlights: Diseased Ruditapes philippinarum show higher abundance of proteins associated with pathogen recognition and neutralization. Proteins associated with energy production metabolisms are more abundant in diseased clams. Healthy clams post-challenge showed higher abundance of proteins associated with redox homeostasis. Resistance to Brown Ring disease may be linked to a balanced redox response and protein structure stability.